Improvement of the physical and mechanical properties of a clay soil through the addition of sand and lime - Boumehraz, Mohammed-Amin; Hamaidia, Achref; Boucetta, Farida; Goudjil, Kamel; Mellas, Mekki (Budownictwo i Architektura / Civil and Architectural Engineering, 2026)
The studied clayey soil exhibits several geotechnical issues, including low bearing capacity and high plasticity. This study aims to improve the physical and mechanical properties of this soil by adding different proportions of sand and lime, or their combination. The studied dosages are as follows: lime (L) at 2%, 6%, and 12%; sand (S) at 5%, 15%, and 30%; and combinations (2% L + 5% S), (6% L + 15% S), and (12% L + 30% S). The laboratory tests performed include Atterberg limits, Modified Proctor, direct shear test, and the California Bearing Ratio (CBR) index. The results show that the addition of sand reduces the liquid and plastic limits, increases the dry density, and decreases cohesion at high content. The incorporation of lime significantly improves the CBR index, increases the plastic limit, and reduces the optimum moisture content. The best results are obtained with the combined treatment (12% L + 30% S), which shows liquid and plastic limits of 39.97% and 19.56%, a maximum dry density of 16.82kN/m³, an optimum moisture content of 16.00%, and a high CBR index of 36.62. Therefore, the lime/sand combined treatment represents an effective solution for improving the geotechnical properties of clayey soils.